Factors associated with post-abortion contraceptive discontinuation - Ana Luiza Vilela Borges; Carolina Cavalcante da Silva Ale; Christiane Borges do Nascimento Chofakian; Osmara Alves Viana; Eveline do Amor Divino; Elizabeth Fujimori (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objectives: To assess factors associated with post-abortion contraceptive discontinuation. Method: This cross-sectional study addressed 111 women aged 18-49 attending Primary Health Care Facilities in São Paulo/SP, Aracaju/SE, and Cuiabá/MT, Brazil, who reported an abortion five years before the interview held in 2015-2017. Kaplan-Meier estimates and Cox Regression were used for data analysis. Results: Oral hormonal contraceptives, male condoms, and injectable contraceptives were the methods most frequently used. The contraceptive discontinuation rate was 41.8% in the 12 months after the abortion. The pill was the method most frequently abandoned (58.3%); male condoms were the method that failed the most (72.7%), and injectable contraceptives were the method most frequently switched (50.0%). Being up to 24 years old, having ten or more years of education, having three or more children, and a desire to wait longer before becoming pregnant again were associated with post-abortion contraceptive discontinuation. Conclusion: Short-acting contraceptive methods were predominant among post-abortion women. The type of discontinuation varied according to the type of method used. The factors associated with contraceptive discontinuation were age, education, parity, and reproductive intention.